Some characteristics of Italian economic development, 1950-1955 - LUTZ, V.C. (PSL Quarterly Review, 2014)
The article analyses some of the less widely discussed features of Italy’s rapid economic expansion of recent years. In particular, the author examines the factors which have helped to determine the high rate of income growth, the pattern of investment, and their effects on employment and productivity. The development process between 1950-1955 seems to have been of a dual character. In one area of the economy - the industrial sectors predominately organised in the form of medium and large-scale units of production, construction, transport, and limited zones within the small-scale, labour intensive and other family-type businesses of manufacturing industry and within commerce - real wage rates, and in some instances also profits, rose substantially. However, additional employment went not so much into this area of the economy as it did into the province of artisan, and other tiny firms, and which was not only poorer to start with, but probably also enjoyed smaller gains in average earnings over the period than did the more prosperous area. The account depicted of the economic development process is thus an uneven one, the increase in income being very largely concentrated among the numbers who were already employed and especially among those who were wage- or profit-earners in the activities that are mostly in the hand of medium- or large-scale firms. The author goes on to examine what would be necessary for the increase in prosperity to be more evenly spread in the future. JEL: O11, O14